2021
DOI: 10.1001/jamanetworkopen.2021.17074
|View full text |Cite
|
Sign up to set email alerts
|

Black and Latinx Community Perspectives on COVID-19 Mitigation Behaviors, Testing, and Vaccines

Abstract: IMPORTANCE Black and Latinx communities have been disproportionately affected by the COVID-19 pandemic, yet little work has sought to understand their perspectives.OBJECTIVE To explore the experiences of Black and Latinx communities during the pandemic to better understand their perspectives on COVID-19 mitigation behaviors (eg, mask wearing), testing, and vaccines. DESIGN, SETTING, AND PARTICIPANTSIn this community-engaged qualitative study conducted with 18 community-based organizations and 4 health care org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 20 publications
1
65
0
Order By: Relevance
“…Racial/ethnic disparities have been observed in all aspects of the COVID-19 pandemic [ 30 ], with communities of color experiencing higher rates of SARS-CoV-2 infection, as well as COVID-19-related hospitalizations and mortality [ 31 , 32 ]. Racial/ethnic disparities in COVID-19 vaccine acceptance at the start of the vaccine rollout threatened to continue this trend [ 33 ], with unclear/unreliable information on COVID-19 vaccines, concerns about research ethics, and access barriers contributing to COVID-19 vaccine hesitancy [ 34 ]. In response, groups from at-risk communities initiated targeted outreach campaigns [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Racial/ethnic disparities have been observed in all aspects of the COVID-19 pandemic [ 30 ], with communities of color experiencing higher rates of SARS-CoV-2 infection, as well as COVID-19-related hospitalizations and mortality [ 31 , 32 ]. Racial/ethnic disparities in COVID-19 vaccine acceptance at the start of the vaccine rollout threatened to continue this trend [ 33 ], with unclear/unreliable information on COVID-19 vaccines, concerns about research ethics, and access barriers contributing to COVID-19 vaccine hesitancy [ 34 ]. In response, groups from at-risk communities initiated targeted outreach campaigns [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several qualitative studies involving black communities found participants expressed concerns about the speed of vaccine development, vaccine safety, and mistrusted government and healthcare initiatives. [25][26][27] A qualitative study that interviewed Veterans and VA staff in three VA medical centers after COVID-19 vaccines became available found several similar concerns to those we report including mistrust of government, though half of the interviewees had received at least one COVID-19 vaccine. 28 Our study had several strengths, including the supplementation of survey data with data from the medical record, mixed quantitative-qualitative methods, in-depth interviews of a subset of respondents and a patient population that is largely African American.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, our findings are consistent with qualitative studies conducted prior to the availability of vaccines. Several qualitative studies involving black communities found participants expressed concerns about the speed of vaccine development, vaccine safety, and mistrusted government and healthcare initiatives [ 27 29 ]. A qualitative study that interviewed Veterans and VA staff in three VA medical centers after COVID-19 vaccines became available found several similar concerns to those we report including mistrust of government, though half of the interviewees had received at least one COVID-19 vaccine [ 30 ]..…”
Section: Discussionmentioning
confidence: 99%